Evaluation of operator visibility in three different cabins type Far-East combine harvesters - Lee, Dae H.; Kim, Yong J.; Choi, Chang H.; Chung, Sun O.; Nam, Yo S.; So, Jin H. (International Journal of Agricultural and Biological Engineering, 2016)
The purpose of this study was to develop and evaluate a visibility evaluation system for the cabin type Far-East combine harvester. The human field of view has been classified into five levels (perceptive, effective, stable gaze, induced, and auxiliary) depending on the rotation of the human head and eye. The divider, reaper lever, gearshift, dashboard, and conveying component were considered as major viewpoints of the cabin type Far-East combine harvester. The visibility of the cabin type Far-East combine harvester was evaluated quantitatively using viewpoints and human field of view levels. The visibility evaluation system for the cabin type Far-East combine harvester consisted of a laser pointer, stepping motors to control the directions of the view, gyro sensors to measure horizontal and vertical angles, and I/O interface to acquire the signals. The visibility evaluation tests were conducted at different postures ('sitting straight', 'sitting with a 15° tilt', 'standing straight', and 'standing with a 15° tilt') for three cabin type Far-East combine harvesters. The LSD (least significant difference) multiple comparison tests showed that the visibilities of viewpoints differed significantly as the operator's posture changed. The results showed that the posture while standing with a 15° tilt provided the best visibility. The average visibility scores at sitting postures were 22.3 (straight) and 24.4 (15° tilt), and the scores at standing postures were 18.7 (straight) and 29.5 (15° tilt). Also, the average visibility scores were observed in order from highest to lowest as reaper lever (44.6), divider (28.7), dashboard (23.1), conveying part (12.2), and gearshift lever (10.1). Most viewpoints of the cabin type Far-East combine harvester were out of the stable gaze field of the view level. Modifications of the cabin type Far-East combine harvester design will be required to enhance the visibility during harvesting operation and to improve safety and convenience of farmers. Keywords: combine harvester, cabin, operator visibility, field of view, evaluation system, ergonomics, safety and comfort DOI: 10.3965/j.ijabe.20160904.1850 Citation: Lee D H, Kim Y J, Choi C H, Chung S O. Evaluation of operator visibility in three different cabins type Far-East combine harvesters. Int J Agric & Biol Eng, 2016; 9(4): 33－44.